THE INFLUENCE OF FINANCIAL BEHAVIOR ON INVESTMENT DECISIONS IN DEPOSIT PRODUCTS IN DIGITAL BANKS FOR THE MILLENNIAL GENERATION IN JAKARTA - Marpaung, Ivan Andeska (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
This study aims to analyze the influence of financial behavior on investment decisions in digital bank deposit products for millennials in Jakarta. This research was conducted in the Special Region of Jakarta from January to February 2025. The population in this study was millennials in the Special Region of Jakarta who invested in digital bank deposits. The sample consisted of 100 respondents using an accidental sampling method. The analytical methods used were descriptive and multivariate analysis using the Smart PLS application version 4.1.1.4. The results of the descriptive analysis indicated that the respondents' responses to the questionnaire regarding aspects of financial behavior were very good, with a total average score of 4.30. The results of the multivariate analysis showed a P-value of 0.000 <0.05, concluding that financial behavior significantly influences investment decisions.